ANALISIS EFISIENSI PRODUKSI DAN KEUNTUNGAN USAHATANI TOMAT DATARAN RENDAH DI KABUPATEN LAMPUNG SELATAN - Berliantara Berliantara; Wan Abbas Zakaria; Dyah Aring Hepiana Lestari (Lampung University, 2016)
This study aimed to analyze: the level of profit and the gain difference of tomato’s lowland farming between members and nonmembers of the farmer group and the factors of production, production scale and efficiency of farm production of lowland tomatoes in both members and nonmembers of farmer group. The number of respondents in this study was taken by cencus method, in which all 62 farmer members and all 35 farmer nonmembers were involved. The research data was collected during October 2015 - January 2016 and was analyzed by R / C ratios, different test (independent t-test), multiple linear regression using the Cobb Douglas production function and NPM / Px ratio. The results showed that tomato farming was profitable business and profitability of farmer group members was higher than nonmembers’ farmers. Land and labor significantly affected the production of tomatoes. Tomato farming of farmer group members currently on the scale of production decreased (decreasing returns to scale) and the nonmembers’ farmers that were in production scale fixed (constant return to scale). The production process tomato farming of both farmer group members and nonmembers farmer groups were not yet efficient.Key Words: efficiency, profits, tomatoes